Evaluation of the nutritive value of fermented corn grain for ruminants - Carvalho, Laura Barbosa de; Mota Neta, Bárbara de Sousa; Rodrigues, Rayane Marques; Fonseca, Alessandra Schaphauser Rosseto; Costa, Ana Cláudia da; Vieira, Karine Padilha Nunes [UNESP]; Guerra, Wanderlei Dias; Abreu, Matheus Lima Corrêa; Galati, Rosemary Lais; Petter, Farah Arruda; Cabral, Luciano da Silva (Wiley, 2024)
The study aimed to evaluate the nutritive value of fermented corn grain (FCG) for ruminants by in vitro and in vivo methods. Free-toxin FCG was evaluated alone or as an ingredient of feedlot diets replacing standard corn grain (SCG) by in vitro gas production technique and by nutritional and performance study using lamb as the animal model. FCG presented similar contents of dry matter (DM), crude protein (CP), neutral detergent fibre (NDF) and starch, but presented higher ash and lower density than SCG. When evaluated in vitro alone, FCG presented higher lag time and lower in vitro dry matter digestibility (IVDMD) than SCG, but as an ingredient of feedlot diets, FCG levels linearly decreased digestion rate and lag time, but linearly increased IVDMD. In an in vivo study, FCG levels had quadratic effects on the intake and digestibility of crude fat, increased feeding time, and decreased resting time of lambs. FCG levels did not affect rumen volatile fatty acid concentration and its profile but trended to linearly increase final body weight, average daily gain and carcase weight. Thus, mycotoxin-free fermented corn grain can be fed to feedlot lambs without negatively affecting the intake and digestibility of nutrients or animal performance.
Keywords: digestibility; Fermented grain; in vitro; in vivo; intake; performance